2015
DOI: 10.1080/13669877.2015.1057204
|View full text |Cite
|
Sign up to set email alerts
|

Preventing black swans: incident reporting systems as collective knowledge management

Abstract: In hazardous industries, disasters are mercifully rare and yet the potential is ever present. For this reason, companies and industries as a whole put substantial effort into gathering information about past small failures and their causes in an attempt to learn how to prevent more serious events. Despite these efforts, recent research has captured how organizations can 'fail' to learn. Disastrous events can become 'black swans' and remain unpredicted despite the existence of information warning of them. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…The study identified several positive associations between examined variables, but particularly unexpected was the relationship between perceived knowledge and personal resilience, as this indicates that the perception of knowledge is more implicated in resilience, rather than actual knowledge. This observation supports the findings of Kupika et al (2019), in which higher individual perceptions of knowledge in the context of climate change were shown to promote resilience [ 23 ].Previous studies presented that perceived risk (as suggested by Paton, Mclure and Burgelt, (2006) and Lopes (2000)) predict greater community resilience [ 16 , 17 ]. The positive associations observed in the current study between perceived safety and perceived knowledge and personal resilience may suggest that beyond risk perception, perceived safety may be a predictor of personal resilience, though this has to be more extensively studied to confirm or predict this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study identified several positive associations between examined variables, but particularly unexpected was the relationship between perceived knowledge and personal resilience, as this indicates that the perception of knowledge is more implicated in resilience, rather than actual knowledge. This observation supports the findings of Kupika et al (2019), in which higher individual perceptions of knowledge in the context of climate change were shown to promote resilience [ 23 ].Previous studies presented that perceived risk (as suggested by Paton, Mclure and Burgelt, (2006) and Lopes (2000)) predict greater community resilience [ 16 , 17 ]. The positive associations observed in the current study between perceived safety and perceived knowledge and personal resilience may suggest that beyond risk perception, perceived safety may be a predictor of personal resilience, though this has to be more extensively studied to confirm or predict this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of disaster preparedness, knowledge may be defined as “the practice of intervening purposefully” to elucidate appropriate function, while perceived knowledge is the belief of oneself concerning the ability to implement such a function [ 17 ]. Findings indicate that the public’s knowledge is thought to have significant influence on its uptake of and adherence to control measures; conversely, knowledge gaps among the population can contribute to the reduced efficacy of control measures implemented [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organizational learning by using CIRS and thereby collective knowledge are prerequisites for succeeding in patient safety. Therefore CIRS should be promoted in every healthcare organization [27].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing consciousness among users, organizers, and experts that risk reporting should be improved, as "better risk reporting is fundamental to healthier governance" [49]. However, how best to balance what the community participants want to see in a risk report with what the organizations are willing to divulge remains unanswered [49]. In particular, organizations are unwilling to reveal anything that might impend a competitive advantage or discuss possible risks in detail if these alarms community participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Effective frameworks use applicable instruments to interconnect and transfer knowledge related to risk to numerous community leaders engaged in disaster decisionmaking [48]. There is an increasing consciousness among users, organizers, and experts that risk reporting should be improved, as "better risk reporting is fundamental to healthier governance" [49]. However, how best to balance what the community participants want to see in a risk report with what the organizations are willing to divulge remains unanswered [49].…”
Section: Literature Reviewmentioning
confidence: 99%